PENURUNAN KADAR BOD DAN AMONIA PADA AIR LIMBAH DOMESTIKMENGUNAKAN TEKNOLOGI BIOFILM DENGAN MEDIA FILTER BUNGA PINUS, POTONGAN BAMBU, DAN BIOBALL - Brian Angga Kusuma; Endro Sutrisno; Sri Sumiyati (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Activitiesofhouseholdsgenerateawastewatereffluent. One effortthat can be takenin minimizing theimpact ofdomestic wastewaterin a simpleandfastas well asprovidingeconomic benefitsto the villagersDalanganprocessingisdoneby usingbiofilmtechnology. Inthisstudy, usethree(3) filtermediaonbiofilmtechnology. Mediaused werepieces ofbamboo, pinefloral, andbioball. Withvariationsresidence time60, 90, 120, 150, 180minutes. Based onthese results, itwas found thattreatmentof domesticwastewaterwithbiofilmtechniqueis able toreducethe concentration ofBODby 95% andammoniaby 42%.